2013
DOI: 10.3233/jad-130428
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HSPA8 and HSPA9 mRNA Expression and Promoter Methylation in the Brain and Blood of Alzheimer's Disease Patients

Abstract: Alzheimer's disease (AD) is the most common form of dementia in elderly. Chaperones may have a crucial role in AD due to their involvement in protein quality control, folding, and degradation. In this study, we investigated the mRNA and promoter DNA methylation levels of two chaperones, HSPA8 and HSPA9, in postmortem brain tissue (entorhinal and auditory cortices and hippocampus) from healthy elderly and AD subjects as well as in peripheral blood of healthy elderly and AD patients. mRNA quantification was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Alternatively, two studies [50, 51] showed no difference in DNA methylation of APP in brain tissue between AD and healthy controls. Fourteen studies found no difference or clear pattern in methylation of the following genes: 12-LOX [34], debrin-like protein gene [34], p450 epoxygenase gene [34], MAPT , PSEN1 , UCHL1 , SST [52], SSTR4 [52], F2RL2 [45], SOD-1 [48] and GRN [53] in brain tissue; PS1 [49], PS2 [49] and tau1 [49], SMARCA 5 [54], CHD1 [54], BDNF [55], SIRT1 [55], PSEN1 [55{Tannorella, 2015 #2823], genes involved in DNA repair [56], genes involved in homocysteine pathway [57], CTSB [58], CTSD [58], DDT [58], TSC1 [58], NRD1 [58] and NDUFA6 [58] in blood cells; HSPA8 [59], HSPA9 [59], ApoE4 [47, 49], SNAP25 [60], SORL 1 , SIRT1 and SIRT3 [49, 54, 60] in both blood cells and brain tissue (Table 2). However, 7 studies showed differences in methylation patterns of CpG sites (within same gene some CpG sites were hypomethylated and some others were hypermethylated, in AD cases) examined at the following genes: SORL1 [61], ABCA7 [61], SLC2A4 [61], BIN1 [61], HSPA8 [59], HSPA9 [59], DR4 gene [62], BDNF4 [43, 44], SIRT1 [49], APP [47], MAPT [47] and GSK3B [47].…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, two studies [50, 51] showed no difference in DNA methylation of APP in brain tissue between AD and healthy controls. Fourteen studies found no difference or clear pattern in methylation of the following genes: 12-LOX [34], debrin-like protein gene [34], p450 epoxygenase gene [34], MAPT , PSEN1 , UCHL1 , SST [52], SSTR4 [52], F2RL2 [45], SOD-1 [48] and GRN [53] in brain tissue; PS1 [49], PS2 [49] and tau1 [49], SMARCA 5 [54], CHD1 [54], BDNF [55], SIRT1 [55], PSEN1 [55{Tannorella, 2015 #2823], genes involved in DNA repair [56], genes involved in homocysteine pathway [57], CTSB [58], CTSD [58], DDT [58], TSC1 [58], NRD1 [58] and NDUFA6 [58] in blood cells; HSPA8 [59], HSPA9 [59], ApoE4 [47, 49], SNAP25 [60], SORL 1 , SIRT1 and SIRT3 [49, 54, 60] in both blood cells and brain tissue (Table 2). However, 7 studies showed differences in methylation patterns of CpG sites (within same gene some CpG sites were hypomethylated and some others were hypermethylated, in AD cases) examined at the following genes: SORL1 [61], ABCA7 [61], SLC2A4 [61], BIN1 [61], HSPA8 [59], HSPA9 [59], DR4 gene [62], BDNF4 [43, 44], SIRT1 [49], APP [47], MAPT [47] and GSK3B [47].…”
Section: Resultsmentioning
confidence: 99%
“…), particularly in the entorhinal cortex and hippocampus (Silva et al . ), and in the substantia nigra in Parkinson's patients (Mandel et al . ; Chu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisomal carnitine (OCTC) levels were higher in the 6-month-old group than the wild-type group, and new therapies acting on peroxisomal metabolism might be developed to prevent cognitive decline and other age-related neurological disorders[53]. (4) Heat shock cognate 71 kDa protein (HSP7C) was upregulated in 6-month-old groups, while its gene level was significantly lower across the three brain regions in AD patients than in controls patients, suggesting their participation in AD pathogenesis [54]. (5) Cooperative expression of leukemia inhibitory factor (LIF) and its receptor (LIFR) in AD hippocampus may indicate a role for LIF in neuronal damage or repair at these sites [55].…”
Section: Mutations In Charged Multivesicular Body Protein 2b (Chmp2b)mentioning
confidence: 99%